A matter of principle or a matter of money? How fairness evaluations change with experimental currencies - Marina Chugunova; Wolfgang J. Luhan (PLoS ONE, 2026)
We investigate how the information on monetary outcomes influences perceptions of fairness of income redistributions. In an economic experiment, participants initially rated the fairness of a redistribution scheme without knowing the exchange rate of experimental tokens to real money. After learning the monetary value of tokens, the participants adjusted their fairness ratings, generally perceiving redistributions that generate higher income for themselves as fairer. As the redistribution itself did not change, our findings suggest that awareness of monetary consequences affects perceptions of redistribution beyond mere self-interest.